Analisis Kinerja Karyawan Bank Syariah berdasar Quality Of Work Life dan Burnout - Nur Ahmad Fadillah; Isfandayani Isfandayani (LPPM Universitas Islam 45, 2023)
The purpose of this study was to determine the effect of Quality of Work Life and Burnout on the performance of Bank BTN Syariah Bekasi Branch Office employees. This research was conducted at Bank BTN Syariah Bekasi Branch Office. This study uses quantitative methods with data analysis techniques using SEM PLS (Structural Equation Model - Path Least Square) analysis. Based on the results of the analysis it is known that Quality of Work Life has a positive and significant effect on the performance of Bank BTN Syariah employees, Burnout also has a positive and significant effect on the performance of Bank BTN Syariah Bekasi Branch Office employees. This shows that the better the quality of work life provided by the company, the higher the performance produced, while the higher the level of burnout management obtained, it can affect the performance of the company's employees.